COMMUNICATION SATISFACTION: A DETERMINANT FOR FACULTY JOB SATISFACTION IN STATE UNIVERSITIES AND COLLEGES IN THE NCR: NA - Butac, Susan (International Journal of Arts, Sciences and Education, 2021)
This study tested the relationship between communication satisfaction and job satisfaction of SUCs’ faculty members in the National Capital Region by analyzing the significance of the different dimensions of Communication Satisfaction with the viewpoint that it is multifaceted. Results of the study initially indicated that the level of communication satisfaction of SUCs’ faculty members in the National Capital Region was significantly satisfied in terms of the Communication dimensions. Then, the study proved the feeling of satisfaction with the communication system, which is a significant variable for job satisfaction. The study found a strong positive relationship found between overall Communication Satisfaction and Job Satisfaction scores. It indicates that when faculty members are satisfied with the communication system they have in their schools, they also tend to feel confident and happy in doing their job. The study also proved that when both communication and job satisfaction are satisfied, a school will have the power to fulfill its goals, mission, vision, and objectives. Thus, enabling it to address the challenges set by the Technology-driven society. This study used the quantitative method of research, particularly the Correlational design. Keywords: communication satisfaction, job satisfaction